Reconsidering tax expenditure estimation: challenges and reforms - Rosanne Altshuler; Robert D. Dietz (Rutgers University, Department of Economics, 2008)
We examine the measurement of tax expenditures and offer recommendations aimed at improving their value to analysts and policymakers. We use calculations from NBER's TAXSIM to illustrate some of the problems with the current methodology for estimating tax expenditures. Unlike most previous work on the topic, we focus on how features of the current tax system complicate and compromise the value of information provided by the tax expenditure budget. Our recommendations for reform include presenting revenue estimates for major tax expenditures, reporting some negative tax expenditures, grouping expenditures by conceptually-linked categories, and establishing an appendix for tax expenditure estimates of permanent versions of expiring provisions and AMT interaction effects.
Keywords: H20; 330; Tax expenditures; tax incentives; tax revenues